2018
DOI: 10.1177/1010428318770953
|View full text |Cite
|
Sign up to set email alerts
|

Collagen analysis by second-harmonic generation microscopy predicts outcome of luminal breast cancer

Abstract: Second-harmonic generation microscopy represents an important tool to evaluate extracellular matrix collagen structure, which undergoes changes during cancer progression. Thus, it is potentially relevant to assess breast cancer development. We propose the use of second-harmonic generation images of tumor stroma selected on hematoxylin and eosin-stained slides to evaluate the prognostic value of collagen fibers analyses in peri and intratumoral areas in patients diagnosed with invasive ductal breast carcinoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…Additionally, patients with metastatic VSCC presented higher COL parameters than those without metastases. These findings agree with our previous study on luminal breast cancer, in which intratumoral COL parameters were reduced in comparison to peritumoral areas 14 . Similarly, patients with parameters associated with more aggressive disease, considered a rare cancer of elderly women, has been increasing in incidence in younger women over the last few decades [16][17][18] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, patients with metastatic VSCC presented higher COL parameters than those without metastases. These findings agree with our previous study on luminal breast cancer, in which intratumoral COL parameters were reduced in comparison to peritumoral areas 14 . Similarly, patients with parameters associated with more aggressive disease, considered a rare cancer of elderly women, has been increasing in incidence in younger women over the last few decades [16][17][18] .…”
Section: Discussionsupporting
confidence: 93%
“…Slides stained with H&E were submitted to the identification and selection of collagen (COL) in the stromal areas adjacent to VIN, in intratumoral stroma, and in normal adjacent tissues. In each case, three areas were selected, and these areas were submitted to SHG analyses at the INFABiC -Unicamp 14 .…”
Section: Second Harmonic Generation (Shg)mentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this, significant attention has been paid to the development of alternative fast and noninvasive ways of obtaining information about biological tissues similar to the results of histological image interpretation. In this context, various optical methods have been proposed, in particular the use of variations in auto-fluorescence properties to detect tumor cells 1,2 or the generation of higher harmonics, which can be used to detect the presence of collagen and elastin 3 . The use of Optical Coherence Tomography (OCT) for such purposes is also attracting much attention, because the characteristic scales of OCT scans occupy an intermediate place between macroscopic imaging (like medical ultrasound) and cell-resolution microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 SHG imaging has been used to study collagen remodeling in BC using a number of analysis methods. [10][11][12] Provenzano et al 13 identified "tumor-associated collagen signatures" (TACS) by assessing fiber density and alignment relative to the tumor boundary during early disease, in-situ breast carcinomas, and invasive BC. Using a manual approach, TACS-3 (fiber alignment orthogonal to tumor boundary) was shown to be prognostic of disease-free survival by Conklin et al 9 Polarization-based SHG reflects the pitch angle of α-helices within the collagen triple helix, which change with BC progression and has been applied to mouse models and human samples.…”
mentioning
confidence: 99%